Flexural behavior of perforated rectangular hollow section cold-formed steel beams: An experimental and numerical study - Chitrarasu Vadivelu; Vaishnavi Prabaharan; Punitha Kumar Akhas (Results in Engineering)
This paper incorporated the flexural behavior of rectangular hollow section (RHS) beams with varying perforation configurations was investigated under bending loads. Both experimental tests and finite element (FE) modeling were employed to analyze load capacity and failure modes. Findings revealed that circular perforations, particularly with a diameter equal to 50 % of the beam's web depth, enhanced bending capacity compared to other diameters of perforations. The number and diameter of perforations were identified as critical factors influencing load-carrying capacity, with beams incorporating smaller perforations demonstrating superior performance. Additionally, the study highlighted a decrease in load-carrying capacity and an increase in deflection with an increasing number of holes, indicating a weakening of structural integrity. This emphasizes the importance of carefully considering hole size in RHS beam design to ensure optimal structural performance. Furthermore, the results underscore the effectiveness of FE analysis in predicting the behavior of perforated RHS beams and provide valuable insights for engineering design and construction practices.